AN ANALYSIS OF LEXICAL AND GRAMMATICAL COHESION IN DIDO'S SONGS - SARI, ANDHI NOVITA (2010)
The study is about describing the lexical and grammatical cohesions which are used in Dido's songs. The objectives of this research are to describe the lexical cohesion and grammatical cohesion in Dido's song lyrics in her Life for Rent album. This research is a descriptive qualitative study which analyzes the elements of cohesions of the song lyrics. The data are sentences which include the lexical and grammatical cohesions found in Dido's song lyrics in Life for Rent album. The writer collects the data by reading the song lyrics, putting sign, and making list on lexical and grammatical cohesion in song lyrics, then describing the lexical and grammatical cohesions toward song lyrics in Life for Rent album by Dido based on Nunan's theory. The result shows that the cohesive devices in Dido's song include the grammatical and lexical cohesions. The grammatical cohesions consists of reference; personal reference, and demonstrative reference, substitution, ellipsis, and conjunction, while the lexical cohesions consists of repetition, synonymy and antonymy. In Dido's songs, the use of lexical cohesions are higher than the gramatical cohesions.